Theoretical Study of Graphene and its Thermal Properties - Ferhat Abderraouf; Abbassi Kodes; Abadi Raouia (My University, 2025)
In this work, we explore the quantum and thermodynamic behavior of graphene placed in a uniform magnetic field while embedded within a curved Anti-de Sitter (AdS) spacetime. Treating the low-energy excitations as massless Dirac fermions, we apply the Nikiforov–Uvarov method to solve the resulting Dirac equation, yielding exact analytical solutions for both the energy levels and wavefunctions. These solutions clearly reflect how curvature and interaction strengths affect the system, leading to noticeable shifts and splitting in the Landau levels as a consequence of the AdS background. With the energy spectrum in hand, we proceed to formulate the system's partition function and derive thermodynamic quantities such as free energy, internal energy, entropy, and heat capacity. The results illustrate how curvature, combined with interaction effects, plays a decisive role in shaping the thermal properties—highlighting phenomena like divergences and signs of thermal instability. Overall, the study deepens our understanding of how graphene-like Dirac systems behave under curved spacetime conditions and sheds light on broader aspects of quantum field theories in deformed geometric settings. في هذا العمل، نستكشف السلوك الكمومي والديناميكي الحراري للجرافين الموضوع في مجال مغناطيسي منتظم أثناء وجوده داخل زمكان منحني من نوع Anti-de Sitter (AdS). من خلال اعتبار الاستثارات منخفضة الطاقة كفرميونات ديراك عديمة الكتلة، نطبّق طريقة نيكيفوروف–أوفاروف لحل معادلة ديراك الناتجة، مما يؤدي إلى حلول تحليلية دقيقة لكل من مستويات الطاقة ودوال الموجة. تعكس هذه الحلول بوضوح كيف تؤثر الانحناءات وقوة التفاعلات على النظام، مما يؤدي إلى انزياحات وانقسامات ملحوظة في مستويات لانداو نتيجة خلفية AdS. بعد الحصول على طيف الطاقة، نتابع بصياغة دالة التقسيم للنظام واستنتاج الكميات الديناميكية الحرارية مثل الطاقة الحرة، والطاقة الداخلية، والإنتروبيا، والسعة الحرارية. توضح النتائج كيف أن الانحناء، بالتزامن مع تأثيرات التفاعل، يلعب دورًا حاسمًا في تشكيل الخصائص الحرارية—مبرزًا ظواهر مثل التشعبات وعلامات عدم الاستقرار الحراري. بشكل عام، يُعمّق هذا البحث فهمنا لكيفية تصرف أنظمة ديراك الشبيهة بالجرافين في ظروف الزمكان المنحني، ويسلط الضوء على جوانب أوسع في نظريات الحقل الكمومي في الأوساط الهندسية المشوهة
Master's theses in chemical engineering 2025
Keywords: : Lagrave – Quantum behavior – Thermodynamic behavior – Uniform magnetic field – Energy as fermions; لجرافين- السلوك الكمومي –السلوك الديناميكي الحراري- مجال مغناطيسي منتظم- الطاقة كفرميونات